PRELIMINARY STUDY OF EMULSION COPOLYMERIZATION OF STYRENE ON NATURAL RUBBER LATEX - Dewi Sondari; Agus Haryono; M Ghozali (Prosiding SNST Fakultas Teknik, 2010)
Polystyrene-graft-natural rubber was prepared by emulsion copolymerization using potassium persulfate and sodium dodecyl sulfate as an initiator and emulsifier respectively. Ratios of monomer styrene to natural rubber were 80:20; 60:40; 50:50, and 40:60 % (v/v). Grafting efficiency could be investigated by extracting the dried sample with methyl ethyl ketone and petroleum ether and then weighting the left over dried sample. The copolymers composition of the polystyrene-graft-natural rubber was obtained using 1H-NMR spectroscopy and  the occurrence of styrene-graft-natural rubber was identified by FTIR spectroscopy. Keywords: Graft Efficiency, natural rubber, emulsion polymerization, copolymerization.